Metabolism and Transport of P Nutrient in the Rhizosphere Zone in Acidic Soils - Niluh Putu Sri Ratmini (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Acidic soils are characterized by low soil pH and high solubility of iron and aluminum affecting the availability of P to be low. The P concentration in the soil solution around the rhizosphere will be influenced by the presence and metabolism of plant roots. Plants get P in the form of inorganic phosphate anion (Pi) from soil solution.  Exudate will affect the activity of microorganisms in rhizosphere and rhizoplan. This paper aimed to review the factors that affect P metabolism in the rhizosphere region. Some of the factors that influence the P metabolism in the rhizophir region are pH, root exudates, microorganisms, temperature, and humidity. Nutrient transformation in the rhizosphere was very narrow. Several things affecting the P transformation include temperature, humidity regime, oxygen, pH and ion availability, sunlight, and CO2. In the soil deficient in P, the plant roots undergo adaptation through changes in root morphology. The P availability in acid soils can be increased by the integration of plants with phosphate solubilizing bacteria or fungi. It is hoped that an understanding of P metabolism in the rhizosphere can determine a more efficient P management effort.